Vanadium doped few-layer ultrathin MoS2 nanosheets on reduced graphene oxide for high-performance hydrogen evolution reaction - Singh A.K.; Prasad J.; Azad U.P.; Singh A.K.; Prakash R.; Singh K.; Srivastava A.; Alaferdov A.A.; Moshkalev S.A. (My University, 2025)
In this paper, we demonstrate a facile solvothermal synthesis of a vanadium(v) doped MoS2-rGO nanocomposites for highly efficient electrochemical hydrogen evolution reaction (HER) at room temperature. The surface morphology, crystallinity and elemental composition of the as-synthesized material have been thoroughly analyzed. Its fascinating morphology propelled us to investigate the electrochemical performance towards the HER. The results show that it exhibits excellent catalytic activity with a low onset potential of 153 mV versus reversible hydrogen electrode (RHE), a small Tafel slope of 71 mV dec-1, and good stability over 1000 cycles under acidic conditions. The polarization curve after the 1000th cycle suggests there has been a decrement of less than 5% in current density with a minor change in onset potential. The synergistic effects of V-doping at S site in MoS2 NSs leading to multiple active sites and effective electron transport route provided by the conductive rGO contribute to the high activity for the hydrogen evolution reaction. The development of a high-performance catalyst may encourage the effective application of the as-synthesized V-doped MoS2-rGO as a promising electrocatalyst for hydrogen production. © 2019 The Royal Society of Chemistry.